Pemanfaatan Lahan Bekas Tambang Batu Bara untuk Pengembangan Sagu - NURHAINI MASHUD; ENGELBERT MANAROINSONG (Buletin Palma, 2014)
Program Pemerintah Daerah Kutai Timur yang dikenal dengan Gerakan Daerah Pembangunan Agribisnis (GERDABANGAGI) ditujukan untuk pemberdayaan masyarakat dan mewajibkan perusahaan pertambangan untuk mereklamasi lahan bekas tambang untuk peningkatan produksi pertanian. Penelitian bertujuan untuk mengidentifikasi kesesuaian lahan bekas tambang batubara untuk pengembangan sagu. Penelitian dilakukan dengan menggunakan metode deskriptif. Penelitian dilakukan tahun 2011 hingga 2013 di lahan bekas tambang batubara PT. Kaltim Prima Coal (KPC) Sangatta, Kutai Timur, Kalimantan Timur. Pengambilan contoh tanah untuk analisis sifat-sifat kimia dan sifat fisik dilakukan di lima lokasi. Hasil penelitian menunjukkan bahwa tingkat kemasaman (pH) tanah di lima lokasi bekas tambang batubara tergolong sangat masam hingga agak masam (4,10-6,46), C-organik rendah-tinggi (0,48-4,82%), kandungan bahan organik rendah-tinggi (1,85-8,30%), ratio C/N rendah-sedang (12,47-22,9), N total sangat rendah-sedang (0,08-0,21%), P tersedia rendah (3,52-7,72 ppm), K tersedia tinggi (11,47-92,80 ppm dan kandungan logam berat Pb rendah (4,87-11,40 ppm). Lahan bekas tambang batubara dapat dikem-bangkan sebagai lahan pertanian menggunakan tanaman sagu dengan pemupukan seimbang. Kata kunci : Kesesuaian, lahan, tambang batubara, pengembangan, sagu.ABSTRACTUtilization of Coal Mined Land for the Development of Sago PalmLocal Government of East Kutai program known as the Regional Movement Agribusiness Development (GERDABANGAGI) aimed for empowering the community and require mining companies to reclaim mined lands to increase agricultural production. The research aims to identify the suitability of the coal mined land for development of sago palm. The study was conducted by using descriptive method. The study was conducted in 2011 to 2013 in coal mining area of PT. Kaltim Prima Coal (KPC), Sangatta, East Kutai, East Kalimantan. Soil sampling for analysis of chemical properties and physical properties carried out in five locations. The results showed that the level of acidity (pH) of the soil at the five sites of a former coal mine very sour to slightly acid (4.10 to 6.46), C-organic low to high (0.48 to 4.82%), the content organic matter low to high (1.85 to 8.30%), the ratio of C/N low to moderate (12.47 to 22.9), total N was very low to moderate (0.08 to 0.21%), available P is very low (3.52 to 7.72 ppm), available K is very low (11.47 to 92.80 ppm) and a low content of heavy metals Pb (4.87 to 11.40 ppm). The cultivated of coal mined land that should be done if it will be used for the development of sago palm is organic fertilizer at five sites, liming and N fertilization at Panle 7 Surya, Dirty Coal, and Sepaso Selatan, P and K fertilization at five study sites. Mined land can be developed as agricultural land use sago plants with a balance fertilizer. Keywords: Suitability;land;coal mining;development, sago.